The origins of the first world war - Mulligan, William, 1975- (New approaches to European history, 2017)
The second edition of this leading introduction to the origins of the First World War. Updated to take account of the latest debates around the war's origins and outbreak, this is an essential classroom text which significantly revises our understanding of diplomacy, political culture, and economic history from 1870 to 1914.